2014
DOI: 10.1097/mpa.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

CD24 and S100A4 Expression in Resectable Pancreatic Cancers With Earlier Disease Recurrence and Poor Survival

Abstract: The expression of markers of EMT and metastasis in PDACs was significantly associated with pathologic features of aggressiveness. CD24 and S100A4 expressions were significant predictors of poor survival; thus, immunohistochemistry for these markers in resected specimens may help to identify PDAC patients with a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
0
23
1
Order By: Relevance
“…A meta-analysis by Li et al which analyzed the relation of CD133 expression and survival in PDAC performed on the group of 908 patients showed shorter survival of individuals with high expression of CD133 comparing to those with low expression of this biomarker [37]. Similarly, high expression of CD24 in PDAC correlated with poor prognosis in the study of Lee et al performed on the group of 67 PDAC with resected tumor [38]. Additionally, an analysis on 96 PDAC patients by Hou et al showed shorter survival in individuals who presented coexpression of CD44 and CD133 [39].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Li et al which analyzed the relation of CD133 expression and survival in PDAC performed on the group of 908 patients showed shorter survival of individuals with high expression of CD133 comparing to those with low expression of this biomarker [37]. Similarly, high expression of CD24 in PDAC correlated with poor prognosis in the study of Lee et al performed on the group of 67 PDAC with resected tumor [38]. Additionally, an analysis on 96 PDAC patients by Hou et al showed shorter survival in individuals who presented coexpression of CD44 and CD133 [39].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of E-cadherin has been reported to exert an unfavorable impact on the overall survival rate of CRC patients (8). However, N-cadherin, a transmembrane protein similar to E-cadherin, has been reported to be abnormally expressed in multiple tumors, including pancreatic (9), gastric (10) and hepatocellular (11) cancers. High expression of N-cadherin predicts poor outcome in patients with superficial urothelial carcinoma and gallbladder cancer (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, S100A4 expression in pancre- atic cancers was significantly associated with earlier tumor recurrence. (20) Although statistical significance was not reached in this study (possibly due to the small number of cases studied), E-cadherin expression loss and S100A4 protein expression were more frequently seen in PanIN-3 lesions associated with CP compared to those without a CP background, supporting the notion that chronic inflammation may contribute to EMT and offering potential clinical target for prevention of metastasis by inhibition of EMT.…”
Section: Discussionmentioning
confidence: 50%